PENERAPAN AKUNTANSI PADA USAHA KECIL MENENGAH - NOVIANTO HUTAGAOL, RENALDO MARTIN (Universitas Katolik Widya Mandala Surabaya, 2012)
This paper describes the application of accounting aimed at small and medium enterprises (SMEs). SMEs recently experienced significant growth, a lot of people who want to make it as an SME business. people try to create their own business or employment due keaadan urgent for that. SMEs therefore easier to develop. However, the development of SMEs experiencing problems often faced by the neglect of financial management, the impact of teraibakannya financial management, SMEs should be able to succeed in the absence of accounting will be bankrupt. Therefore, accounting is necessary for the owner to manage finances and be aware of income for a year as well as the performance of its business, the owner can make decisions that will be the continuation of its business. Therefore, accounting is necessary for small and medium businesses due to favorable accounting for SMEs